SOCIAL MEDIA DARLING : SEBUAH KONSTRUKSI SOSIAL ATAS REALITAS - Diego Diego; Imam Havifi; Yayuk Lestari; Sarmiati Sarmiati (Metacommunication: Journal of Communication Studies, 2023)
The phenomenon of social media darling is an individual who is used as a reference for social media users in forming discourse on something. Social media darling or known as influencers try to create content that can attract the attention of audiences. The many content ideas presented by influencers are not always true or in accordance with reality. Influencers try to construct the views and perceptions of their fans by building the reality they create through content uploaded to the Instagram application. This research is intended to further examine how social construction is created by influencers in the city of Padang so that fans are always loyal to wait for and enjoy the content they produce. The use of qualitative methods in this study is intended to explore the phenomenon of social media darling in depth and comprehensively. The results of this study indicate that Praz Teguh as an influencer from Padang City has a great influence in shaping the social construction of society, especially young people in Padang City. The wide number of followers, creativity, authenticity, and consistency in creating content has made Praz Teguh able to bind his followers to always wait for the works that are presented.